PERAN MARKETING PUBLIC RELATIONSDALAM MEMPERTAHANKAN LOYALITAS PELANGGAN SERVICEMOTOR DI AHASS KINOKI MOTORINDO SRAGEN - Hafidah, Hafidah (Solidaritas, 2024)
In facing business competition, companiesnot only need to increase sales, but also must retain existing customers by maintaining good relationships with them. Rapid development, especially in the motorcyclerepair industry, adds challenges and threats for businesses to compete and survive. This research examines the role of Marketing Public Relations at Ahass Kinoki Motorindo Sragen in maintaining customer loyalty. The main focus of this research is: How is the role of Marketing Public Relations in maintaining customer loyalty at Ahass Kinoki Motorindo Sragen? This research is presented with a qualitative descriptive approach, using data collection methods through interviews, observation, and documentation, and following a purposive samplingprocedure.Dataanalysiswas conductedinthree stages: datareduction, data presentation, and conclusion verification. The results showed that some of the Marketing Public Relations roles applied in maintaining customer loyalty at Ahass Kinoki Motorindo Sragen include problem analysis, planning, action, and evaluation. In addition, additional strategies such as pull strategy and pass strategy are used. However, there are obstacles faced in implementing these roles and strategies, both from internal and external factors of the company.